Quality Comparison Between Edge Detection Method Based On Scale Sobel Canny and Good Image - Kamiswara A; Sukoco A (International Conference on Engineering and Technology Development (ICETD), 2017)
Image processing is the processing of two-dimensional images through digital computers "(Jain, 1989). In image processing there are several steps that must be done,namely image acquisition, image enhancement (pre-procesing), image segmentation, representation and description , then introduction and interpretation. Edge detection (edge detection) is one of the stages in image processing that aims to find out the pattern of image objects that kemudaian can be used in segmentation and extraction features on the image. In edge detection there are several methods that are quite popular among them is the canny and sobel method. In the process and result detection canny is superior with value 3,889 than sobel which only have value 3,667 based on goodness of image recommended from ITU 500-11.